Environmentally Sustainable Supply Chain Practices, Organisation Culture on Firm Performance. A Mediation Approach - Mohammed, Zurah Chepkoech; Ngeno, Vincent; Lagat, Charles (International Journal of Emerging Trends in Social Sciences, 2019)
Sustainability is increasingly turning into a strategic business project that firms are recognizing that sustainable carry outs can be economical and ought to make fresh income streams as well as enhance client and worker gratification. Despite this, sustainability and performance of firms have received little research attention. Using Natural Resource-Based View and stakeholder theory, research main purpose was to determine the mediating effect of organization culture on the association amid environmentally sustainable supply chain practices and firm performance. This study used descriptive statistics, Pearson product-moment correlation, and Structural Equation Modeling (SEM) to test the hypothesis. Data collected from 281 Kenyan manufacturing firms were used to test study hypotheses. From bias-corrected bootstrapping Structural Equation Modeling, results showed that organization culture variable fully mediates the association amid environmentally maintainable supply chain methods on the performance of manufacturing firms. Thus, the study infers that a strong organizational culture in the organization leads to the enhanced implementation of environmentally sustainable supply chain practices in the organization which in turn increases the performance of manufacturing firms. Without organization culture, these practices may go unheeded and not contribute to improved performance of manufacturing firms in Kenya. Consequently, this study recommends that the managers of these firms should build an organizational culture with environmental concerns in all their processes. This study hence contributes to theory and practice by the inclusion of organizational culture and also extends natural resource-based view and stakeholder theories of a firm.